Combining ability analysis for fruit yield and related traits in Brinjal (Solanum melongena L.) using Line × Tester mating design - Imamuddin, S; Neelima, R; Hitaishi, K; Kuldeep; Aakash, K D; Udit, J; Raju, Y R; Satvinder , S; Rajesh, S K; Dhirendra, S (Plant Science Today, 2025)
Brinjal (Solanum melongena L.) is a significant vegetable crop, widely cultivated and consumed in almost every household across India. Enhancing fruit production per unit area requires a focus on key traits such as early maturity, enhanced plant vigor and increased fruit yield. Consequently, crop breeding programs emphasize the development and commercialization of brinjal hybrids tailored to regional needs. Effective crop improvement hinges on selecting suitable parental lines and employing precise crossing techniques to generate hybrids with desirable agronomic traits. The present study was conducted to assess the combining ability for fruit yield and related traits in brinjal. The experiment was carried out during the Kharif season of 2023 and the summer season of 2024 at the Vegetable Research Centre, G.B. Pant University of Agriculture and Technology, Pantnagar, Uttarakhand, India. A randomized block design (RBD) with three replications was utilized. The study involved 30 hybrid combinations derived from 13 brinjal genotypes, employing a line × tester mating design with 10 lines and 3 testers. Results indicated that among the parental genotypes, PBGL-5 (88.11), PBGL-7 (85.02) and Swarna Abhinav (67.80) demonstrated high general combining ability (GCA) for fruit yield and related traits. Among the hybrid combinations, Pusa Kaushal × Pant Samrat (153.16), Pusa Ankur × Kashi Uttam (126.37) and PBGL-5 × Pant Rituraj (116.77) exhibited superior specific combining ability (SCA) effects. These results highlight the potential of the identified parents and hybrids as promising genetic resources for future breeding programs aimed at hybrid development and yield enhancement. In conclusion, the identified genotypes and crosses with favorable GCA and SCA effects can serve as valuable candidates for breeding programs to develop high-yielding, region-specific brinjal hybrids. This study underscores the importance of systematic parental selection and hybrid evaluation in advancing brinjal crop improvement initiatives.